2021
DOI: 10.1016/j.bbih.2021.100331
|View full text |Cite
|
Sign up to set email alerts
|

Lost in translation. The quest for definitions of treatment-resistant depression with a focus on inflammation-related gene expression

Abstract: Approximately one third of individuals with major depressive disorder (MDD) do not respond to antidepressant treatments; but what does treatment-resistant depression (TRD) mean? With this article, I aim to provide an overview of the clinical and operational criteria currently used to define TRD, highlighting core gaps in knowledge and open questions to be addressed in order to drive future research in the field. Importantly, a better definition of TRD must include a better characterization of the biological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Also, taking into consideration the small number of participants in the majority of the reviewed studies, additional and larger prospective trials will be needed to explore the prognosis of treatment responses in TRD. Additionally, the investigation of specific blood-based, peripheral biomarkers should concurrently target factors from different pathophysiological pathways and be combined with (epi-)genetic, psychometric, and environmental factors, acknowledging also the individual medical histories of patients (e.g., immune/metabolic comorbidities and exposure to childhood trauma) in order to help establish sensitive and specific biomarkers for the different biological sub-phenotypes of the disorder [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, taking into consideration the small number of participants in the majority of the reviewed studies, additional and larger prospective trials will be needed to explore the prognosis of treatment responses in TRD. Additionally, the investigation of specific blood-based, peripheral biomarkers should concurrently target factors from different pathophysiological pathways and be combined with (epi-)genetic, psychometric, and environmental factors, acknowledging also the individual medical histories of patients (e.g., immune/metabolic comorbidities and exposure to childhood trauma) in order to help establish sensitive and specific biomarkers for the different biological sub-phenotypes of the disorder [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The term TRD was first introduced 50 years ago [ 18 ]. However, there has been no unanimous consensus reached with respect to the exact definition of TRD [ 13 , 19 , 20 , 21 , 22 ]. For instance, a recent systematic review mentioned over 150 different definitions of TRD in the relevant literature [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in the context of treatment resistant depression these genes may predict lack of response to particular treatments. It is suggested that instead of selecting genes a priori , that the entire transcriptome be analyzed based on whole-genome approaches, which may reveal gene candidates not previously associated with depressive disorders ( Sforzini, 2021 ) . Additionally, using an absolute, rather than a relative quantitative approach will better allow for the identification of defined thresholds of mRNA values of pro-inflammatory cytokines ( Mariani, 2021 ) .…”
Section: Introductionmentioning
confidence: 99%